2006
DOI: 10.1051/0004-6361:20065691
|View full text |Cite
|
Sign up to set email alerts
|

Explosive heating of low-density coronal plasma

Abstract: Context. This paper addresses the impulsive heating of very diffuse coronal loops, such as can occur in a nanoflare-heated corona with low filling factor. Aims. We study the physics associated with nanoflare heating in this scenario and aim to determine whether there exist any observable signatures. Methods. We derive an analytical model in order to gain some simple physical insights into the system and use a one dimensional hydrodynamic model that treats the electrons and ions as a coupled fluid to simulate n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
95
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
2
1

Relationship

4
4

Authors

Journals

citations
Cited by 86 publications
(99 citation statements)
references
References 22 publications
(26 reference statements)
3
95
1
Order By: Relevance
“…Non-equilibrium ionization could contribute to surpressing the emission too (Bradshaw & Cargill 2006). In this picture, the non-thermal broadening of the spectral lines would appear as it does in real flares, with the hot AR core loops corresponding to post-flare loops observed in their cooling phase.…”
Section: Summary and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Non-equilibrium ionization could contribute to surpressing the emission too (Bradshaw & Cargill 2006). In this picture, the non-thermal broadening of the spectral lines would appear as it does in real flares, with the hot AR core loops corresponding to post-flare loops observed in their cooling phase.…”
Section: Summary and Discussionmentioning
confidence: 99%
“…For example, measurements of non-thermal velocities of 40 km s −1 or so would tend to support a chromospheric evaporation or Alfvén wave turbulence explanation, though clearly they could not discriminate between them. Conversely, the nanoflare model may predict high non-thermal velocities, but these may only be apparent immediately after the energy release, and could be difficult to detect due to the low emission measure (EM) of any hot plasma, a problem that may be further exacerbated by non-equilibrium conditions (Bradshaw & Cargill 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Müller, Hansteen, and Peter (2003) investigated the effects of non-equilibrium ionisation on condensation in transition region spectral lines. Bradshaw and Cargill (2006) found significant departure from equilibrium in models of coronal loops heated by nanoflares. In this work we factor in the effects of non-equilibrium ionisation by using the established HYDRAD code (Bradshaw and Cargill, 2013) for our simulations and modelling.…”
Section: Introductionmentioning
confidence: 92%
“…Recent interest in the detectability of dynamic heating events localised in the solar corona (Bradshaw & Cargill 2006;Reale & Orlando 2008), believed to be responsible for its high temperature, has brought the importance of non-equilibrium ionisation (NEI) states to the forefront of research concerning the nature of coronal heating. One example of such heating is the reconnection of adjacent magnetic field lines that have become twisted and braided in the corona due to the random motions of their photospheric footpoints.…”
Section: Introductionmentioning
confidence: 99%
“…One example of such heating is the reconnection of adjacent magnetic field lines that have become twisted and braided in the corona due to the random motions of their photospheric footpoints. Often called nanoflares (Parker 1988;Cargill 1993Cargill , 1994Cargill 1997Klimchuk 2006), with reference to the fraction of energy released in comparison to a large scale flare, models have shown that they may heat the corona to temperatures ≥10 7 K (Cargill & Klimchuk 2004;Patsourakos & Klimchuk 2005, 2006Bradshaw & Cargill 2006;Klimchuk 2006).…”
Section: Introductionmentioning
confidence: 99%